Would Christ Have Become Incarnate Had Adam Not Fallen? - Lindholm, Stefan (Journal of reformed theology, 2015)
In this paper I examine the notion of Christ as Mediator apart from sin in the reformed scholastic theologian, Jerome Zanchi (1516–1590). Calvin developed a rich notion of Christ as Mediator but left an ambiguous heritage to his followers—it led some later interpreters to think of it as imply that the incarnation would have happened apart from sin. In the first part, I lay out some background and positions and in the second I deal with what I argue is a misunderstanding of Zanchi’s use of Christ as Mediator (that it implies incarnation apart from sin). In the third part I will further explore Zanchi’s notion of Christ as Mediator and make comparisons with Thomas Aquinas, John Calvin and Francis Turretin.